Columnea blancoi (Gesneriaceae), a new species from the central Pacific region of Costa Rica - Jiménez Vargas, José Esteban (2023)
We describe and illustrate a new species of Columnea from the Central Pacific region of Costa Rica. Columnea blancoi sp. nov. is morphologically similar to Columnea canarina, from Panama which it can be distinguished by having stems that are flaky and sericeous distally, ovate bracts, entire, green and shorter calyx lobes, yellow corolla that is glandular-pilose externally, with a marginal purple-red line 1–2 mm wide on all lobes internal and externally, and a shorter ventral corolla lobe and style. A taxonomic description, illustrations, a distribution map, conservation status, and comments on how C. blancoi differs from other morphologically related species are provided.